The Legal Effectiveness of Juvenile Diversion: A Study of the Indonesian Juvenile Justice System - Daud Rismana; Ali Maskur; Rifi Maria Laila Fitri Permonoputri; Hariyanto Hariyanto; Hajar Salamah Salsabila Hariz (Khazanah Hukum, 2025)
This study aims to evaluate the legal effectiveness of diversion mechanisms within Indonesia’s juvenile justice system, particularly in relation to the state’s commitment to restorative justice principles. Although a comprehensive legal framework is in place—namely Law No. 11 of 2012 and Supreme Court Regulation (PERMA) No. 4 of 2014 (Peraturan Mahkamah Agung)—the implementation of diversion remains limited, with only 14.1% of juvenile cases resolved through this mechanism. This gap reveals a significant disconnect between legal norms and practical enforcement. The study employs a normative-qualitative legal research method, utilizing document analysis of statutory regulations and institutional reports from the Ministry of Law and Human Rights, the Indonesian Child Protection Commission (KPAI), the Directorate General of Corrections, as well as secondary sources including academic literature, media coverage, and official documentation. Thematic analysis was applied to identify structural, cultural, and institutional barriers in the implementation of diversion. The findings highlight three major issues: (1) regional disparities in the application of diversion, especially between urban centers and disadvantaged (3T) areas; (2) structural obstacles, including a shortage of trained personnel, lack of proper mediation facilities, and weak interagency coordination; and (3) the persistence of a retributive and legalistic legal culture among both law enforcement officials and the general public, which impedes the acceptance of restorative approaches. This study makes a significant contribution to the discourse on juvenile justice reform by emphasizing the need for systemic support and cross-sectoral collaboration to ensure the effective realization of diversion. Policy implications include the strengthening of training programs, infrastructure development, and public legal education. The originality of this research lies in its integrative evaluative framework, which combines legal, institutional, and socio-cultural analysis, offering a comprehensive assessment of the effectiveness of diversion in Indonesia.